Synthesis of Nanocrystals of Dysprosium Benzenedicarboxylate Metal-Organic Framework for Sensing of Nitroaromatic Explosives - Wang, Wei; Qiu, Ling-Guang; Shao, Guo-Quan; Wu, Yun; Wang, Yu (Asian Journal of Chemistry, 2012)
In this paper, we present a morphology-controlled synthesis of nanoscale metal-organic frameworks (NMOFs) by using a surfactant-assisted method for fluorescent sensing of nitroaromatic explosives. Nanocrystals of dysprosium-containing MOF, Dy-BDC (1) (BDC = 1,4-benzene dicarboxylate), was synthesized under different conditions. Transmission electron microscopy (TEM) images of Dy-BDC reveal that size and shape of nanocrystals can be tuned by varying the reaction time. Fluorescence sensing of 2-nitrotoluene, 4-nitrotoluene, 2,4-dinitrotoluene and 2,6-dinitrotoluene by using Dy-BDC nanorods have been studied. The results indicate that Dy-BDC nanocrystals are highly sensitive to nitroaromatic compounds. The results may be helpful for designing novel fluorescence sensor for the sensing of explosives.